Kinematic Analysis of WMR Tracked by a Camera Vision System - Alwan, Hasan M.; Atiyah, Qasim A.; Hasan, Hussein A. (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper presents a study of a nonholonomic differential drive wheeled mobile robot (WMR) of the type (BOE-Bot). In this paper, two aims are presented: the first is the study of the WMR movement on a specific trajectories to get the desired goals positions and the second is the evaluation of the kinematic performance factor of the WMR movement. The kinematic model of the robot movement in terms of the robot wheels velocity is studied by making the robot to move on the desired trajectories. The determination of the actual robot centre position in two dimensions (X) and (Y) is done by tracking the movement of a red point located above the robot by using a fixed camera attached to the ceiling. The position error between the theoretical and actual WMR position vectors is studied and calculated in global and local coordinates' frames. The values of the position error percentage ratios when the robot moved on a (S-shape) trajectory were higher than its values when the robot moved on a (straight-line) trajectory because of the existence of a gyroscopic torque resulted from the WMR circular movement around an axis perpendicular to the axis of the WMR wheels rotation. Finally, the kinematic performance factor of the WMR movement is evaluated depending on the position error in the global coordinate.